A Bolder Step towards Privacy Protection in Hong Kong: A Statutory Cause of Action. (1st January 2014) - Mo, Yun Ching Jojo; Koo, A. K. C.
Abstract: Privacy is an important value which is internationally recognised as worthy of protection. However, it has been under constant challenge for a number of reasons including changes in technology which facilitate informational and other forms of surveillance and privacy-invasive media practices. Because of its multi-faceted nature, privacy is typically regulated by a variety of different means. Data protection laws seek to ensure the fair handling of personal information. Criminal sanctions are used to outlaw more serious invasions of privacy, including certain breaches of communications privacy and uses of surveillance devices. Assorted civil actions are relied on to protect broader interests in privacy. However, the piecemeal nature of privacy protection is often found to be inadequate and victims frequently lack appropriate remedies. Therefore, many common law countries either provide for or are actively considering the introduction of civil remedies to specifically address general privacy issues. There has also been active consideration of measures to regulate media organisations, especially in the light of the Murdoch scandal in the United Kingdom. The inadequacies in the law have prompted calls for law reform in Hong Kong, and recommendations have been made in the report on Civil Liability for Invasion of Privacy (2004). It examined the need of individuals to be able to seek civil remedies for unwarranted invasion of privacy. In it the Law Reform Commission of Hong Kong (HKLRC) proposed the introduction of specific statutory torts of privacy to cover acts and conduct frustrating the reasonable expectation of an individual's privacy. It proposed that a person, who invaded another's privacy by intruding upon their solitude or seclusion, or by intruding into their private affairs or concerns, should be liable in tort. It also recommended another tort for invasion of privacy arising out of public disclosure of private facts. This article focuses on the issue of civil liability and analyses the inadequacies of existing laws and regulatory regimes and attempts to come up with a model that is most suitable for Hong Kong. It takes the HKLRC's recommendations as its starting point but refines and modifies them, drawing on the insights that have since become available from the work of other law reform bodies and further developments in overseas case law.